2006
DOI: 10.1189/jlb.1105622
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine-specific phospholipase C (PC-PLC) is required for LPS-mediated macrophage activation through CD14

Abstract: Lipid rafts, composed of sphingolipids, are critical to Toll-like receptor 4 (TLR4) assembly during lipopolysaccharide (LPS) exposure, as a result of protein kinase C (PKC)-zeta activation. However, the mechanism responsible for this remains unknown. The purpose of this study is to determine if LPS-induced TLR4 assembly and activation are dependent on the sphingolipid metabolite ceramide produced by phosphatidylcholine-specific phospholipase C (PC-PLC) or CD14. To study this, THP-1 cells were stimulated with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…In addition, MPS synovial cells have elevated levels of the prosurvival lipid, S1P, contributing to the enhanced proliferation rate. Changes in the production of the signaling lipids, ceramide and S1P, are known consequences of LPS signaling, 26,27,37 supporting our central hypothesis. Osteopenia, in addition to other bone lesions, has been observed in some of the MPS disorders, including MPS VI.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, MPS synovial cells have elevated levels of the prosurvival lipid, S1P, contributing to the enhanced proliferation rate. Changes in the production of the signaling lipids, ceramide and S1P, are known consequences of LPS signaling, 26,27,37 supporting our central hypothesis. Osteopenia, in addition to other bone lesions, has been observed in some of the MPS disorders, including MPS VI.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have indicated that the binding of LPS to CD14 activates a cascade of lipid messengers and protein kinase Cz (PKCz) prior to the recruitment of TLR4 into lipid rafts (9,10). Single and double gene silencing of TLR4, CD14, and/or PKCz in spheroids was specific and did not alter any proteins other than the target molecules ( Supplementary Fig.…”
Section: Lps/tlr4-induced Epithelial Proliferation Is Prevented By Ermentioning
confidence: 99%
“…The binding of LPS to CD14 on the lipid raft domain activates a cascade of lipid messengers and protein kinase Cz (PKCz) to recruit TLR4 to form a complex with CD14 (9,10). The transfer of LPS to TLR4/MD2 subsequently initiates cytoplasmic signaling, resulting in the production of proinflammatory cytokines, such as myeloid differentiation factor (MyD88), MAPK, and inhibitor of kB (IkB)/nuclear factor-kB (NFkB; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inhibition of the enzyme by D609 leads to the disappearance of both the CD16 receptor and PC-PLC from these cholesterol-rich structures. D609 is a wellknown inhibitor of PC-PLC and is widely used to investigate the role of this enzyme in several cellular processes, such as LPS-mediated macrophage activation and B lymphocyte activation through CD38 signaling [24,25].…”
Section: Discussionmentioning
confidence: 99%